Tanytarsus deimos group (Chironomidae, Diptera) for two distinctive species from the Neotropics - Giłka, Wojciech; Dantas, Galileu P.s.; Andersen, Trond; Armitage, Brian J. (Zootaxa, 2024)
Two species of the genus Tanytarsus van der Wulp, 1874 are described: T. deimos Giłka, Dantas et Andersen, sp. nov. (Mexico, Panama) and T. phobos Dantas, Giłka et Andersen, sp. nov. (Peru). Small adult males having wings with a high venarum ratio, unpaired tibial spurs on mid and hind legs, a hypopygial anal point lanceolate without spinulae or bars, a digitus with a well-developed basal tubercle bearing a long seta, a stout median volsella, and a gonostylus distinctly shorter than the gonocoxite, are a set of characters common to the two close species for which a new group is here proposed.